2014
DOI: 10.1007/978-3-319-09614-8_19
|View full text |Cite
|
Sign up to set email alerts
|

A Perspective on Chemoprevention by Resveratrol in Head and Neck Squamous Cell Carcinoma

Abstract: Head and neck squamous cell carcinoma (HNSCC) accounts for around 6% of all cancers in the USA. Few of the greatest obstacles in HNSCC include development of secondary primary tumor, resistance and toxicity associated with the conventional treatments, together decreasing the overall 5-year survival rate in HNSCC patients to ≤50%. Radiation and chemotherapy are the conventional treatment options available for HNSCC patients at both early and late stage of this cancer type malignancy. Unfortunately, patients res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 69 publications
0
22
0
Order By: Relevance
“…Since resveratrol can cause DNA damage to squamous cell carcinoma in the head and neck area [202], causing p53-dependent apoptosis [203], and inhibiting accumulation of hypoxia-inducible factor-1α and vascular endothelial growth factor (VEGF) expression [204], resveratrol can be used as either a chemopreventive agent [205, 206] or a therapeutic one, improving cytotoxic irradiation-based therapy, by decreasing cyclin B, cyclin D, CDK2, CDK4, and the anti-apoptotic molecule Fas-associated protein with death domain-like IL-1β-converting enzyme-inhibitory protein (FLIP), Bcl-2, and SVV [178, 207209]. Resveratrol may also improve the cytotoxicity of 5-fluorouracil [210, 211] (Table 1; Fig.…”
Section: Resveratrolmentioning
confidence: 99%
“…Since resveratrol can cause DNA damage to squamous cell carcinoma in the head and neck area [202], causing p53-dependent apoptosis [203], and inhibiting accumulation of hypoxia-inducible factor-1α and vascular endothelial growth factor (VEGF) expression [204], resveratrol can be used as either a chemopreventive agent [205, 206] or a therapeutic one, improving cytotoxic irradiation-based therapy, by decreasing cyclin B, cyclin D, CDK2, CDK4, and the anti-apoptotic molecule Fas-associated protein with death domain-like IL-1β-converting enzyme-inhibitory protein (FLIP), Bcl-2, and SVV [178, 207209]. Resveratrol may also improve the cytotoxicity of 5-fluorouracil [210, 211] (Table 1; Fig.…”
Section: Resveratrolmentioning
confidence: 99%
“…The accumulating evidence suggests that resveratrol targets and kills cells that cannot repair their own damaged DNA, thereby preventing them from becoming cancerous . At the molecular level, studies have indicated that resveratrol targets the protein DNA polymerase.…”
Section: Killing the Killersmentioning
confidence: 99%
“…The cancer chemoprevention approach exploits nontoxic natural or synthetic pharmacological agents to prevent, block or reverse the multistep processes of carcinogenesis [9,10]. Chemopreventive agents inhibit the invasive development of cancer by affecting the three defined stages of carcinogenesis namely initiation, promotion and progression which are induced by carcinogens through genetic and epigenetic mechanisms [11,12].…”
Section: Introductionmentioning
confidence: 99%